Friars to Military Guard. The Historic Value of the Lima’s Barbones Barrack (1825-1879) - Jara Boza, Yonatan (2021)
It is the historic Barbones Barrack ubicated out of the ancient viceregal walls of Lima in El Agustino district. This military complex has an important role in the traditional Cambio de Guardia in the Main Square as the headquarters of the official military guard but it also reminds a massive historical fact especially as the Convent and Hospital of the nearly extinct religious order of Betlemitas. This research tries to explain the issue between the Church and the Military Force in terms of infrastructure approach in the beginning of the Republic and having the ancient Barbones Convent next Barbones Barrack as a model.